IL-4 Receptor-Alpha Signalling of Intestinal Epithelial Cells, Smooth Muscle Cells, and Macrophages Plays a Redundant Role in Oxazolone Colitis - Jennifer Claire Hoving; Roanne Keeton; Maxine A. Höft; Mumin Ozturk; Patricia Otieno-Odhiambo; Frank Brombacher (Mediators of Inflammation)
A hallmark of ulcerative colitis is the chronic colonic inflammation, which is the result of a dysregulated intestinal mucosal immune response. Epithelial barrier disruption which allows the entry of microorganisms eventually leads to more aggressive inflammation and potentially the removal of the colon. We have previously shown that the T helper- (Th-) type 2 cytokines, Interleukin- (IL-) 4 and IL-13, mediate CD4+ T cell- or B cell-driven inflammation in the oxazolone-induced mouse model of ulcerative colitis. In contrast, mice deficient in the shared receptor of IL-4 and IL-13, IL-4 receptor-alpha (IL-4Rα), on all cells develop an exacerbated disease phenotype. This suggests that a regulatory role of IL-4Rα is required to protect against severe colitis. However, the cell populations responsible for regulating the severity of disease onset through IL-4Rα in colitis are yet to be identified. By deleting IL-4Rα on specific cell subsets shown to play a role in mediating colitis, we determined their role in a loss of function approach. Our data demonstrated that the loss of IL-4Rα signalling on intestinal epithelial cells, smooth muscle cells, and macrophages/neutrophils had no effect on alleviating the pathology associated with colitis. These results suggest that IL-4/IL-13 signalling through IL-4Rα on nonhematopoietic intestinal epithelial or smooth muscle cells and hematopoietic macrophage/neutrophils has a redundant role in driving acute oxazolone colitis.